Kualitas Pelayanan Fiskus, Kesadaran Pajak dan Kepatuhan Wajib Pajak: Peran Moderasi Kondisi Keuangan Wajib Pajak - Frinola Minovia, Arie; Yulistia Muslim, Resti; Karimi, Kasman (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study examines the relationship between the quality of fiscal services, the level of tax awareness, and taxpayer compliance by including taxpayer financial conditions as a moderating variable in the analysis model. Taxpayer compliance is very important for increasing tax revenue and is crucial in financing national development. This study focuses on Individual Taxpayers (WPOP) registered at the Padang 1 Tax Office (KPP), where data was collected using convenience sampling and resulted in a sample of 98 respondents from 115 questionnaires distributed. Using SEM-PLS, the results of this study reveal that improvements in the quality of services provided by tax officials and high levels of tax awareness play a significant role in encouraging taxpayer compliance. Conversely, the financial condition of taxpayers does not show a significant influence on the relationship between the quality of tax services and tax awareness with taxpayer compliance.